2003
DOI: 10.1063/1.1606516
|View full text |Cite
|
Sign up to set email alerts
|

Infrared spectroscopic study on the Langmuir–Blodgett films of merocyanine dye–arachidic acid–n-octadecane ternary system

Abstract: Articles you may be interested inOligo(vinylidene fluoride) Langmuir-Blodgett films studied by spectroscopic ellipsometry and the density functional theorySize and molecular configuration of dye aggregates in mixed Langmuir-Blodgett films based on merocyanine dyeWe have studied the mobility and the orientation of the hydrocarbon chain in the Langmuir-Blodgett films of merocyanine dye ͑MS͒-arachidic acid (C 20 ) -n-octadecane (AL 18 ) with the molar mixing ratio ͓MS͔:͓C 20 ͔:͓AL 18 ͔ϭ1:2:x (xϭ0,1,2,3,4,5) by me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 14 publications
1
34
0
Order By: Relevance
“…The solid and dotted lines denote A ∥ and A ⊥ , respectively. In Figure a, a blue-shifted peak with sharp absorption is observed at 505 nm, which is ascribed to H-aggregation. The absorption maximum at 505 nm shows the dichroic ratio with R < 1, where R is defined as A ∥ / A ⊥ . This tendency of R originates from the MS 18 side-by-side arrangement in the H-aggregate 13-20 and the flow orientation effect .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The solid and dotted lines denote A ∥ and A ⊥ , respectively. In Figure a, a blue-shifted peak with sharp absorption is observed at 505 nm, which is ascribed to H-aggregation. The absorption maximum at 505 nm shows the dichroic ratio with R < 1, where R is defined as A ∥ / A ⊥ . This tendency of R originates from the MS 18 side-by-side arrangement in the H-aggregate 13-20 and the flow orientation effect .…”
Section: Resultsmentioning
confidence: 99%
“…The MS 18 concentration in the ternary system was on the order of 10 -4 M. An LB trough of the USI system (Fukuoka, Japan) was used. The preparations of the aqueous subphase containing cadmium chloride (CdCl 2 ) and sodium hydrogen carbonate (NaHCO 3 ) were the same as those reported previously. , After the chloroform solution was spread on an air−water interface, the monolayers were directly transferred to both sides of 13 × 38 mm 2 mica and CaF 2 substrates by the standard vertical dipping method at a surface pressure of 25 mN/m. The raising velocity of the mica substrate was 2.5 mm/min for the deposition of the monolayer, whereas the raising and dipping velocities of the CaF 2 substrate were 2.5 mm/min for up to 3 × 2 layers and then 25 mm/min afterward.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The minimum of E st for an antiparallel arrangement is always located at sϭ0 and an H aggregate should be formed if E st solely determines the molecular arrangement. In fact, Hirano et al [33][34][35] reported that DS forms H aggregates in L films under certain preparation conditions. Therefore, other interaction͑s͒ must compensate this electrostatic disadvantage of the J aggregates.…”
Section: ͑1͒mentioning
confidence: 99%
“…Hirano et al [11] compared the aggregation number and the other structural parameters of the J-and H-aggregates of the merocyanine-arachidic acid-n-octadecane ternary system estimated using the point dipole model and the extended dipole model referring to the deconvoluted spectra. Morita et al [12] indicated that the J-aggregate is accompanied by the thermal motion of the hydrocarbon chains of the merocyanine-arachidic acid-n-octadecane ternary system, and that the H-aggregate is accompanied by the highly packed state of the hydrocarbon chains of MS, suggesting that the aggregate formation is controlled by the state of hydrocarbon chain packing. Saito [13] indicated the application of MC-LB films mixed with AA to photoelectric conversion devices in expecting high efficiency photoelectric conversion, because the packing density of MC molecule increased and the defects of LB films decreased to lead an increase of the built-up proportion of J-aggregates in the MC-LB films by adding AA to the MC-LB films.…”
Section: Introductionmentioning
confidence: 98%